The Role of Audit Firms in Spreading Depositor Contagion - Beck, Matthew J.; Nicoletti, Allison K.; Stuber, Sarah B. (The Accounting Review, 2022)
ABSTRACT Auditor credibility is important in the banking industry due to the opacity of bank assets and the use of financial statements by external parties to facilitate monitoring. Depositors monitor and discipline bank behavior, but they can also contribute to the spread of shocks from one bank to another. We argue that depositors perceive bank failure as an audit failure, which reduces their assessment of auditor credibility. We document that exposure to failure through the audit firm is associated with lower uninsured deposit growth following the failure, consistent with depositors perceiving failures as a negative signal of auditor credibility. We further document that this association is stronger when depositors perceive connection to failure to reflect a pervasive issue within the audit firm. Collectively, our results suggest that depositors consider accounting signals at other banks in assessing financial reporting credibility. JEL Classifications: G21; M41; M42.